Uji Stabilitas Fisik Sabun Mandi Cair Ekstrak Etanol Daun Ketapang (Terminalia Catappa L.) Dan Kulit Nanas (Ananas Comosus (L.) Merr) - Dewi, Asiska Permata; Shufyani, Fahma; Darmadi, Darmadi (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Soap cleans the skin from dirt or bacteria. The plants that can be used in liquid shower soap are ketapang leaf and pineapple skin. The purpose of this research was to make a liquid shower soap formulated with the extract of ketapang leaf and pineapple skin and then test its physical stability for 4 weeks storage. The liquid shower soap of ketapang leaf and pineapple skin was made of three extract variations namely F1 (2%), F2 (4%) and F3 (6%). The physical stability test of liquid shower soap covered organoleptic, pH, homogeneity, foam height, voscosity, density, hedonic, and supply irritation. The result of organoleptic test in F1, F2, and F3 had brownish color, distinctive extract smell, and in the form of liquid supply. pH in F1, F2, and F3 for 4 weeks of storage was in the interval of 6,5-7,2. The result of homogeneity test showed that all formulas were homogeneous and the test of foam durability in the range of 76,92% - 97,14%. Then viscosity test at F1, F2, and F3 was in the range of 10,95 poice - 43,19 poice and the density was in the range of 1,01 - 1,03 mg/ml. The hedonic test in F1 was likeable, F2 and F3 were rather likeable and all formulas of liquid shower did not cause irritation in the usage. Based on the test results, it can be concluded that the liquid shower soap produced has fulfilled the requirement of physical supply quality based on The National Standard of Indonesia (SNI).